1978
DOI: 10.1002/pssa.2210480108
|View full text |Cite
|
Sign up to set email alerts
|

Static wall structure in bubble films under large in-plane fields

Abstract: The domain wall structure in a magnetic bubble domain film is considered for the case in which an in‐plane field is applied which is either perpendicular or parallel to the wall plane. It is shown that a fairly simple analytical solution to the problem of the static wall structure may be obtained when the in‐plane field exceeds μ0Ms because it is then possible to assume that the problem is one‐dimensional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1978
1978
1981
1981

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…The static structure of the domain wall under such conditions has been the subject of a previous paper [14] where it was shown that the magnetostatic field from the two doniaiiis lying upon either side of the wall could be neglected when the in-plane field was such that pOMs < B, < p0M,Q. A solution to the problem of the static wall structure was then obtained in which 171 was a function of y only, rotating in (y, z ) across the wall region, M always having a component parallel to y.…”
Section: ( 2 )mentioning
confidence: 99%
See 4 more Smart Citations
“…The static structure of the domain wall under such conditions has been the subject of a previous paper [14] where it was shown that the magnetostatic field from the two doniaiiis lying upon either side of the wall could be neglected when the in-plane field was such that pOMs < B, < p0M,Q. A solution to the problem of the static wall structure was then obtained in which 171 was a function of y only, rotating in (y, z ) across the wall region, M always having a component parallel to y.…”
Section: ( 2 )mentioning
confidence: 99%
“…It is implicit in the Landau-Lifshitz model that 1 < M , and A/M9 is identical to the now well established Gilbert damping parameter [16]. The vector P in (3) is the total effective magnetic field made up from the exchange, anisotropy, magnetostatic and applied fields [14]. The magnetonieclianical ratio is written as -lyI because this ratio is negative in nearly all materials.…”
Section: Dynamicsmentioning
confidence: 99%
See 3 more Smart Citations